1978
DOI: 10.1295/polymj.10.331
|View full text |Cite
|
Sign up to set email alerts
|

Stiff Chain Behavior of Poly(terephthaloyl-trans-2,5-dimethylpiperazine) in Dilute Solution

Abstract: A number of narrow-distribution fractions of poly(terephthaloyl-trans-2,5-dimethylpiperazine) (PTDP) ranging in Mw (weight-average molecular weight) from 5,000 to 300,000 were prepared, and their molecular weights, z-average mean-square radii of gyration Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…Because of this feature, the separately estimated q and ML values are not very accurate. Nevertheless, the Ml value of 310 nm-1 is compatible with the chemical structure of PIDP20 and close to those (300-360 nm-1) determined by Motowoka et al21,22 for poly-(phthaloyl-frans-2,5-dimethylpiperazine) and poly(terephthaloyl-ircms-2,5-dimethylpiperazine), the two polyamide isomers of PIDP, in various solvents. Our q of 1.2 nm in NMP is much smaller than the previously estimated values13 for PIDP in other solvents (4.9 nm in mcresol and 3.1 nm in trifluoroethanol).…”
Section: Discussionsupporting
confidence: 88%
“…Because of this feature, the separately estimated q and ML values are not very accurate. Nevertheless, the Ml value of 310 nm-1 is compatible with the chemical structure of PIDP20 and close to those (300-360 nm-1) determined by Motowoka et al21,22 for poly-(phthaloyl-frans-2,5-dimethylpiperazine) and poly(terephthaloyl-ircms-2,5-dimethylpiperazine), the two polyamide isomers of PIDP, in various solvents. Our q of 1.2 nm in NMP is much smaller than the previously estimated values13 for PIDP in other solvents (4.9 nm in mcresol and 3.1 nm in trifluoroethanol).…”
Section: Discussionsupporting
confidence: 88%
“…For this reason, we include the three isomeric polyamides in the present discussion, pursuing the following aims; (i) We wish to check the use of the method based on eq 11 for less stiff chains than those discussed so far. (ii) By analyzing the data for PIDP, we hope to find out if the method allows the effects of chain stiffness and expansion to be separated, (iii) Motowoka et al17,35 have found that the theory of Yamakawa and Fujii cannot account for the experimental data for PPDP and PTDP at < 2 X 104. We wish to explore the possibility of detecting such deviations by the proposed method.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the persistence length of the remaining one of the three isomers, i.e., the meta-linked poly(isophthaloyltrans-2,5-dimethylpiperazine) (PIDP), we measured z-average mean-square radii of gyration (S 2 )z and intrinsic viscosities [ry] of narrow-distribution samples of this polymer over a range of weightaverage molecular weight Mw from 3.7 x 10 3 to 2.4 x 10 6 g mol-1 • This maximum M w was several times as large as any one of those treated in Motowoka's studies on PPDP 1 and PTDP. 2 Except at relatively low Mw, the data exhibited features usually observed for long flexible polymers in good solvents. In this paper, we report these experimental results and consider their significance in the study of semiflexible polymers in dilute solution.…”
mentioning
confidence: 83%
“…For any fraction, the [17] value in m-cresol is larger than that in TFE by a constant factor of 1.45 ± 0.08. It is of interest that Motowoka et al 2 found [IJ1m-cresol/['7hFE to be 1.42 ± 0.08 for the PTDP fractions examined. In Figure 6, the molecular weight dependence of [17] for PIDP in m-cresol is compared with that for PPDP 1 and PTDP 2 in the same solvent.…”
Section: Viscometrymentioning
confidence: 96%